The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1097/00003246-199702000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood sample oxygen tension on blood glucose concentration measured using an enzyme-electrode method

Abstract: Blood glucose values measured using a bedside glucometer in this study were influenced by the sample oxygen tension. We used a corrective equation which improved the accuracy of estimating blood glucose values to a clinically acceptable range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…[14][15][16][17][18][19] Increased pO 2 values can occur in patients requiring artificial respiration. 9,11,20 In this study, at ''high'' pO 2 values the GOD systems showed a negative bias for the measurement results compared with those at pO 2 values approximately 70 mm Hg. This is in line with several other studies reporting that some GOD systems underestimate BG values when measurements were performed on blood samples with increased pO 2 values.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…[14][15][16][17][18][19] Increased pO 2 values can occur in patients requiring artificial respiration. 9,11,20 In this study, at ''high'' pO 2 values the GOD systems showed a negative bias for the measurement results compared with those at pO 2 values approximately 70 mm Hg. This is in line with several other studies reporting that some GOD systems underestimate BG values when measurements were performed on blood samples with increased pO 2 values.…”
Section: Discussionmentioning
confidence: 46%
“…This is in line with several other studies reporting that some GOD systems underestimate BG values when measurements were performed on blood samples with increased pO 2 values. 8,9,11,21 In such studies, measurements on adjusted venous blood samples with pO 2 values >100 mm Hg or in critically ill patients/patients undergoing surgery with increased arterial pO 2 values up to approximately 600 mm Hg resulted in a negative bias. Probably, the competition between dissolved oxygen in the blood sample and the electron acceptor on the biosensor of test strips leads to a diminished chemical reaction when the blood samples' pO 2 value is increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies reported that some test strips, especially those with glucose oxidase enzyme reaction, are sensitive to oxygen and that high oxygen concentrations may lead to system results lower than the true value. [29][30][31][32][33] Most of the published system accuracy evaluation studies either do not evaluate samples with BG concentration <80 and ≥300 mg/dl (or not sufficient numbers) or use venous blood. [34][35][36][37][38][39] Main reasons for doing so are most likely the difficulty of designing a controlled human study or an adequate procedure to obtain capillary blood samples in hypoglycemic and hyperglycemic ranges.…”
Section: Discussionmentioning
confidence: 99%
“…However, oxygen, a confounding variable, can affect glucose meter measurements. [1][2][3][4][5] In our previous study, 6 we observed that changes in blood oxygen tension (Po 2 ) can affect glucose measurements on handheld glucose meters with some of latest test strips. A whole-blood/plasma glucose analyzer, the YSI, served as the reference method.…”
Section: Introductionmentioning
confidence: 99%